Refractariedad al tratamiento con carbonato de litio en pacientes con trastorno bipolar - Sánchez, Ricardo; Jaramillo, Luis E.; Arciniegas, Fabián (Revista de la Facultad de Medicina, 1999)
Refractoriness to the treatment with lithium is a phenomenon not sufficiently studied and that seems to be increasingly frequent. The available literature makes more emphasis in the therapeutic options than in the risk factors for this clinic situation. In this case - control study, 14 patients that showed refractoriness to the treatment with lithium, identified in the Mental Health Unit of the Hospital San Juan de Dios in Santafé de Bogota between 1995 and 1997, were compared with a group of not refractory patients. The group of refractory patients was characterized by: smaller time elapsed between the two last disease episodes, more psicosocial deterioration during the last year, high frequency of personality disorder and greater number of previous episodes treated with lithium. Sociofamiliar support and stable couple relationships were less frequent in this group. Implications of these findings and the limitations of the study are discussed.